Mesio-distal crown width in permanent dentition amongst adolescent population of Province II of Nepal - Jaiswal, Alok Kumar; Parajuli, Umesh; Bajracharya, Manish; Singh, Binita (Journal of Gandaki Medical College-Nepal, 2020)
Background: The purpose of this study was to gather normative data on the mesio-distal crown dimensions amongst adolescent population of Province II, Nepal, to make an accurate diagnosis and treatment planning in orthodontics. It will also be useful in various clinical disciplines of dentistry including basic dental and anthropological research.Materials and Methods: Samples were selected Full form OPD of M B Kedia Dental College, Birgunj, Nepal. Total numbers of participants were 120, out of which 60 males and 60 females were selected after initial examination aged between 11 to 23 years. Subjects with all permanent teeth erupted (except second and third molar) without any history of previous orthodontic treatment and with no dental anomalies were included in this study. The alginate impressions were made by the well trained dental surgeon. Digital vernier calliper providing measurements to ± 0.01millimeter(mm) was used to measure the mesio-distal dimension of all teeth.Results: The mean, range and standard deviation were calculated for the size of the teeth. Independent t-test was used to compare between male and female population. The significance level was set at p value